مشكل الآية 62 من سورة البقرة والآية 69 من سورة المائدة دراسة تطبيقية (The problem of verse 62 of Surat Al-Baqarah and verse 69 of Surat Al-Ma’idah: An Empirical Study) - بنت صالح بن ناصر الدغيثر رشا (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
يهدف هذا البحث إلى بيان معنى الآية 62 من سورة البقرة، والآية 69 من سورة المائدة، والتوفيق بين أقوال المفسرين في توجيه المشكل فيهما، وتفسير المتشابه بالمحكم، وقد اتبعت في هذا البحث المنهج التحليلي الاستقرائي، والجمع بين الأقوال في تفسير الآيتين، وخلصت إلى النتيجة الآتية، وهي أن المعنى الصحيح للآيتين: أما قبل بعثة النبي محمد صلى الله عليه وسلم فالإيمان الحق هو اتباع النبي المرسل في ذلك الزمان لمن بعث إليه نبي، أو البقاء على الحنيفية ودين إبراهيم لمن كان في زمن الفترة، وأما بعد بعثة النبي صلى الله عليه وسلم فلا يقبل إلا الإسلام الذي جاء به محمد صلى الله عليه وسلم والإيمان به واتباعه واعتقاد نسخ ما قبله من شرائع الأنبياء، فمن لم يؤمن بمحمد صلى الله عليه وسلم فهو من الخاسرين. الكلمات المفتاحية: المشكل، أهل الكتاب، اليهود، النصارى، الصابئون. Abstract: This research aims to clarify the meaning of verse 62 of Surat Al-Baqarah and verse 69 of Surat Al-Ma’idah, reconciling the sayings of the commentators in directing the problem in them, and the interpretation of the similar in terms of the arbitrator. The following: The correct meaning of the two verses: As for before the mission of the Prophet Muhammad, may God’s prayers and peace be upon him, the true faith is to follow the Prophet sent at that time to the one to whom a prophet was sent, or to remain on the Hanifiyyah and the religion of Abraham for those who were in the time of the period, and after the mission of the Prophet, may God bless him and grant him peace. He, peace and blessings of God be upon him, accepts nothing but the Islam that Muhammad, may God’s prayers and peace be upon him, brought, belief in it and following it, and belief in abrogating what came before it from the laws of the prophets. Whoever does not believe in Muhammad, may God’s prayers and peace be upon him, is one of the losers. Keywords: The problem, People of the Scriptures, Jews, Christians, Sabians.